Potential of glyburide to reduce intracerebral edema in brain metastases. (April 2014) - Boggs, Drexell Hunter; Simard, J Marc; Steven, Andrew; Mehta, Minesh P
<x xml:space="preserve">Abstract</x> Metastatic disease to the brain results in significant morbidity because of edema in the central nervous system. Current anti-edema therapies are either expensive or result in unwanted long-term side effects. Sulfonylurea receptor 1 (Sur1) is a transmembrane protein that, when activated in the central nervous system, allows for unregulated sodium influx into cells, a process that has been linked to cytotoxic edema formation in ischemic stroke, subarachnoid hemorrhage, spinal cord injury, traumatic brain injury, and, most recently, brain metastases. In this focused review, we explore preclinical data linking Sur1 channel formation to development of edema and reference evidence suggesting that the antidiabetic sulfonylurea drug glyburide (a Sur1 inhibitor) is an inexpensive and well-tolerated agent that can be clinically tested to reduce or prevent malignancy and/or treatment-associated edema.